A video game level analysis model proposal - Almeida, Samuel (2012)
This paper presents a preliminary model proposal for the analysis of video game level scenarios consisting of four elements: video game, players, metrics, and gaming experience. The selection of parameters from each of these elements defines a specific video game level analysis context. Initial validation of the model is being carried out with a First-person shooter video game and selected metrics (including eye movement behavior) to understand player behavior (both interactive and visual) within a game level. An additional analysis technique based on visual representation techniques applied in this validation context is also described. After validated, this model may be applied in the analysis of player behavior in game levels, in several different situations predicted in the model itself. Information acquired from the application of this model may posteriorly be used in the design (or redesign) of game levels and scenarios driven for optimal use which should generate a greater gaming experience.